Exploring Knowledge of Gene-Based Nutrition Services Among Indonesian Nutritionists: Gambaran Pengetahuan Ahli Gizi Tentang Pelayanan Gizi Berbasis Gen di Indonesia - Zulfa, Ifana Fitria; Aji, Arif Sabta; Rahayu, Herwinda Kusuma; Paramashanti, Bunga Astria; Hafizhah, Rafiqah Dwita; Putri, Sintia Aurilia; Alfiana, Rina; Farhan, Alfina Ulfah; Surendran, Shelini (Universitas Airlangga, 2023)
Background: Individuals possess unique genes that influence their susceptibility to diseases and their response to dietary interventions. The emergence of nutritional genomics has made it possible to identify disease predispositions and mitigate risks through gene-based dietary guidance. Consequently, understanding gene-based nutrition services is crucial for nutritionists, as it facilitates the integration of genetic insights into dietary recommendations. Objectives: This study aims to evaluate the familiarity of dietitians in Indonesia with gene-based nutrition services. Methods: Employing a qualitative approach with a phenomenological orientation, this study was conducted in DKI Jakarta, Jawa Barat, Jawa Tengah, Jawa Timur, and DI Yogyakarta. Purposive sampling was employed, involving a total of seven nutritionists. Data were gathered through in-depth interviews conducted both in person and online via Zoom meetings. Thematic analysis was carried out utilizing Nvivo 12.0. Results: The knowledge of nutritionists regarding nutritional genomics is limited. While they could explain fundamental concepts, their understanding lacked depth. Similarly, their comprehension of gene-based nutrition services was restricted, leading to uncertainties about their role in such services. Nutritionists generally expressed positive attitudes towards gene-based nutrition services, recognizing their significance and advocating for their provision by relevant agencies. There was a strong interest among nutritionists in offering gene-based nutrition services and a willingness to expand their understanding of nutritional genomics. Conclusions: The knowledge of nutritionists regarding gene-based nutrition services remains insufficient. There is a need for nutritionists to undergo training, attend seminars, and enhance their understanding of nutritional genomics in academic settings.